La fabrique de la ville en transition - Fenker, Michael; Grudet, Isabelle (éditions Quae, 2022)
Faced with the ecological imperative, how have public action and professional and citizen practices been positioned and reconfigured in France in the fields of urban planning and architecture since the 2000s? How have the injunctions of sustainable development and ecological transition been translated into public policies, mediation mechanisms and project situations? This book analyses, from a comprehensive and critical perspective, the political, professional, citizen, scientific and media spheres that have mobilised and interacted to negotiate this societal shift. It describes the tensions that have arisen between an approach to the ecological city that is still marked by normative and productivist logics, and another based on the idea of sobriety and the capacity of the citizen-inhabitant to control the transformation of his or her living environment. In an economic context strongly influenced by neo-liberal logics, it questions the very notion of 'factory' which has progressively replaced that of production in the fields of urban transformation since the beginning of the third millennium. This book brings together articles by a group of researchers - sociologists, geographers, urban planners, architects - who are members of different scientific laboratories in France and who have actively contributed to this reflection. It is intended for academics and students of architecture, urban planning or urban engineering, as well as for practitioners and actors in charge of developing ecological urban policies.